Exploring the Impact of Students Hostel Life on Academic Performance - Igbal, Mohammed Rasheed; Iqbaal, Ubaadah Bin; Kumar, Shaista Snehal; Devi, Shaleshni Radhika; Kumar, Saleshni (Journal of Ecohumanism, 2024)
Impacts of hostel life on students healthy and overall academic performance in majority cases is multifaceted. Students decide to become hostel residency due to the demanding need for better education, which pushes students away from their comfort zone and drags them to a new home which supports and facilities their growth especially if areas where there is shortage of basic facilities in the particular area in which they were initially staying in. Hostel life has numerous benefits bounded to it such as peer support which helps boost their academic journey, access to essential facilities, and an environment which supports and creates an environment where students can delicate their time towards studies. However, along with this advantages there are numerous challenges that students residing in hostels have to face which includes peer pressure, social disturbance and financial related issues and in one way or another the implication of effective hostel management and various hostel related policies can help mitigate the issues which students face as this particular body houses will ensure that an inclusive and supportive environment is created that will help carter students with diverse needs and various backgrounds are looked after. Along with this collective efforts from education stakeholders and other institutions support is needed that can ensure that hostel related stress in effectively handled and students’ academic performance is not compromised.